The Effect Of Compensation, Work Environment, Career Development On Job Satisfaction With Employee Work Motivation As An Intervening Variable In Rs X - Felicia Nathania; Yanuar Ramadhan; Idrus Jus’at (Syntax Corporation Indonesia, 2023)
Hospitals are HR-intensive organizations because of the many kinds of professions and the number of workers engaged in them. Human resources in a hospital consist of health workers (including doctors, nurses, pharmacists, analysts, nutritionists, physiotherapists, radiographers, medical recorders) and non-health personnel (finance, administration, personnel, security, and so on). In the hospital management system, a strategy is needed to manage human resources. This study used quantitative descriptive research methods using linear regression tests, Pearson correlation tests, and path analysis. The study used 93 respondents. The results of this study show that there is a significant influence between compensation, work environment, and career development stimultan on job satisfaction through employee work motivation. The results of the linear regression test showed the t value for compensation was 1.050, the work environment was 10.960, career development was 5.205, work motivation was 3.654. The results of the Pearson correlation test to work motivation for compensation variables were 0.283, work environment was 0.724, career development was 0.386. The results of the Pearson correlation test to job satisfaction for compensation variables were 0.312, work environment was 0.734, career development was 0.415, work motivation was 0.791. Hospital management is expected to improve and improve factors related to compensation, work environment, career development in order to increase work motivation so as to increase job satisfaction.